To study the effectiveness of outsource human skill at national institute occupational safety and health, Bangi , Selangor / Nurul Ain Fathiah Hamzah - Hamzah, Nurul Ain Fathiah (2018)
Purpose of this study is to determine the effectiveness factor of outsource human skill at National Institute Occupational Safety and Health, Bangi. In leading a rapid growth in the industries, many companies trying to operate efficiently while achieve their goals. But in order to meet the objectives, they are facing with lack of a resources such as human skill. So, to overcome this problem, they need to outsource human skill to fulfil the company requirement in order to make the company operation going smoothly. There are few factors will impact to the company effectiveness when they outsource human skill at National Institute Occupational Safety and Health, Bangi, which are organization capabilities, interaction process, relationship intensity and company performance. These elements are important to measure the company condition in the future. Reason for doing this research to know how effective facing by the company when they are continuously outsource the human skill in a long period. This survey was conducted by collect primary data which is researcher do a survey by questionnaire for a staff and client at the National Institute Occupational Safety and Health (NIOSH), Bangi. 100 respondents are involved to answer the questionnaire. The data was analyzing by using SPSS. Findings suggested that that relationship intensity and company performance have positlve relationshlp with the effectiveness of outsource human skill at National Institute Occupational Safety and Health, Bangi.